Agricultura familiar e assessoria técnica: uma análise da experiência do projeto Dom Helder Câmara no território sertão do Apodi/RN - Gurgel, Rosane Fernandes de Sousa (2016)
This research has as its theme the technical assistance offered to farmers by the state of Rio Grande do Norte. People who are dedicated to agriculture and inhabit the Sertão territory from Apodi / RN, located in the semiarid region of northeastern Brazil, live daily with the adverse weather conditions, high levels of poverty and rainfall unevenly distributed. In an attempt to minimize the negative impacts of this reality technical advice may constitute a possibility of overcoming difficulties. Seeking to contribute to the formulation of a model that meets more closely the needs of this population, this study aims to develop a comparative analysis between conventional technical advisory model of EMATER and that one developed by Dom Helder Câmara Project - PDHC in settlements and rural communities of Sertão territory from Apodi / RN, assessing the perception of the beneficiaries of both, and also identify the existence of different social technologies of technological packages. It is a qualitative and desk research. Data were obtained from PDHC reports, IFAD (International Fund for Agricultural Development) and manual operations of the research sites, visits to the Local Unit Supervision - (ULS) of PDHC in the Apodi Territory (TSA) and field research .69 interviews were realized by a conducted guided by a semistructured script with leaders of the Apodi Territory, executing agencies and / or partners and direct beneficiaries both ATER of PDHC as the EMATER. The survey results, after benchmarking, although point better performance of PDHC, especially in the operating methodology, at the available structure and in the composition and performance of their technical teams also show the need to improve effective services and policies technical assistance available in the territory, considering the experimental project experience as PDHC, consistent with the local knowledge of farmers and technologies appropriate to the reality of the semiarid region